Tinjauan Holistik Pertumbuhan Dan Perkembangan Peserta Didik; Implikasinya Terhadap Penyelenggaraan Pendidikan - wahidah, emma (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
This study focuses on the basic concept of inclusive growth and development of students and its implications for educational activities in the context of descriptive analysis. Educators should not be taboo about the progress of growth and development of students because learning that pays attention to the rate of change in students will be useful in actualizing effective learning strategies as well as developing the potential that exists within them. In this research, the method used is a qualitative study with a literature review approach. Based on the information obtained, research results were obtained in the form of basic theories of student growth and development, development as a holistic process viewed from biological, cognitive and psychosocial aspects, as well as student growth and development regarding the educational process with implications. The urgency of this research is to obtain a comprehensive understanding regarding a particular topic while building a theoretical foundation for further research.